(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2015)
This work will look at the question of the relationship between classical order and order of modernity in the work of Paul Philippe Cret (1876-1945), the French-American architect, a student of Jean-Louis Pascal and Julien Guadet at the Ã©cole des Beaux-Arts in Paris. In the wake of tradition and vocabulary of the Beaux-Arts, Cret’s civic architecture represented in its conception by the â€œAttic orderâ€, one of the five canonical orders, conceived for modern life, without the explicit and philological or direct use, creating an anti-dogmatic program that he will define, in fact, â€œNew Classicismâ€. The text will cover more in detail the Folger Shakespeare Library built in Washington D.C. (1929-1932), whose expansion and renovation was entrusted (1977-1983) to the firm Cox & C. In the structure the problem of the contemporary interpretation of classicist architecture is obvious, of an architecture in which the idea of classical order lives. The text refers to the critical success of Cret’s work and the direct and indirect influences that his investigations had on the modern classicism of such architects as Marcello Piacentini, Albert Speer, Adalberto Libera, Ludovico Quaroni, Luigi Moretti. And on the further migrations of his stripped classicism through the works and writings of his Philadelphia students: in an Anglo-Saxon context (Louis Kahn), and a Chinese context (Liang Sicheng).